Peran Hukum Administrasi Negara dalam Menjamin Kepentingan Umum: Studi Kasus Implementasi Kebijakan Pelayanan Publik di Indonesia - Zees, Sri Wahyuni (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This is a new Administrative law plays an important role in safeguarding public interest. In the context of public services, the succes of policy implementation largely depends on the role of administrative law in ensuring public interest. Indonesia, as a country with a large and heterogeneous population, requires effective and efficient public service policies. However, there are various challenges and obstacles that must be overcome in implementing public services policies. Therefore, this research aims to explore the role of administrative law in ensuring public interest through a case study of the implementation of public services policies in Indonesia. Thus, this study is expected to provide a better understanding of how administrative law can support effective and efficient public service policies in Indonesia.